Robust Hobserver-Controller for 2-D Fmii Systems with the Protocol of Round-Robin and Randomly Occurring Uncertainties - Acosta-Barbosa, K; Zoulagh, T (Institute of Electrical and Electronics Engineers Inc., 2022)
An H state observer-controller for the two-dimensional system Marchesini-Fornasini second model (FMII) is addressed by considering the Round-Robin (R-R) protocol based on the quantization process. Additionally, the under-consideration system features uncertainties of norm-bounded type, which are managed by two stochastic variables fulfilling the Bernoulli distribution. The R-R protocol is a sort of static scheduling, it grants communication access rights to sensors in chronological order. The objective of this letter is to design an H, observer-controller that guarantees the mean square stability of the 2-D error system. Sufficient conditions are derived for H performance analysis and design by involving some auxiliary variables that lead to reduced conservatism. Thereafter, a linear matrix inequality is proposed to allow a one-step design of the observer-controller gains. In the end, an illustrative example borrowed from literature is suggested to highlight the efficiency of the proposed approach. © 2022 IEEE.
Keywords: State estimation; Round-Robin protocol; Two-dimensional systems; Randomly occurring uncertainties; Logarithmic quantization